Challenges to CDM Implementation in Uganda: A Critical Analysis of Legal and Policy Barriers - Namanya, Bernard (Informa UK Limited, 2008)
This paper examines the legal and policy barriers to the Clean Development Mechanism (CDM) implementation in Uganda. Although CDM has been perceived as an opportunity through which developing countries can achieve sustainable development while at the same time helping to mitigate climate change, it remains unclear as to whether CDM will in fact deliver the much anticipated sustainable development benefits in light of the current global trends in CDM investments. By February 2007, only approximately 1.5% of the total registered projects were in Africa and one project was in Uganda. The main study methodology has been library research.